A Prospective Longitudinal Cohort to Investigate the Effects of Early Life Giardiasis on Growth and All Cause Diarrhea - Donowitz, Jeffrey R. (Clin Infect Dis, 2016)
Background. Growth stunting in children under 2 years of age in low-income countries is common. Giardia is a ubiquitous pathogen in this age group but studies investigating Giardia's effect on both growth and diarrhea have produced conflicting results. Methods. We conducted a prospective longitudinal birth cohort study in Dhaka, Bangladesh, with monthly Giardia and continuous diarrheal surveillance. Results. 629 children were enrolled within the first 72 hours of life, and 445 completed 2 years of the study. 12% of children were stunted at birth with 57% stunted by 2 years. 7% of children had a Giardia positive surveillance stool in the first 6 months of life, whereas 74% had a positive stool by 2 years. The median time to first Giardia positive surveillance stool was 17 months. Presence of Giardia in a monthly surveillance stool within the first 6 months of life decreased length-for-age Z score at 2 years by 0.4 (95% confidence interval, −.80 to −.001; P value .05) whereas total number of Giardia positive months over the 2-year period of observation did not. Neither variable was associated with weight-for-age Z score at 2 years. In our model to examine predictors of diarrhea only exclusive breastfeeding was significantly associated with decreased diarrhea (P value <.001). Concomitant giardiasis was neither a risk factor nor protective. Conclusions. Early life Giardia was a risk factor for stunting at age 2 but not poor weight gain. Presence of Giardia neither increased nor decreased odds of acute all cause diarrhea.